PARTISIPASI PEREMPUAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH DALAM PEMBENTUKAN PERATURAN DAERAH DI KOTA SEMARANG - DWI ESTY WIDYASTUTI, Amiek Soemarmi, Retno Saraswati (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Regional House of Representatives (Parliament) is the representative body for realizing the sovereignty of the people in the area. The function of Parliament as an institution representative of all the people in the region is a vehicle for the implementation of democracy in the area that serves as an element of the regional administration.The presence of women legislators of Semarang are limited, making the existence of a large role and influence policy making in parliament should be able to do them. In the context of equality, women should also have had a hand in the formulation of policy, but if the quality of women legislators could not cope with the swift struggle of equality, this will certainly be a bad thing for the struggle.Because, let alone equality policy, a line of women's issues rarely touched. It means that the presence of women legislators is questionable. On this basis, the authors take the title